Data for "Techno-economic feasibility assessment of calcium looping combustion using commercial technology appraisal tools" - Michalski, Sebastian; Hanak, Dawid P.; Manovic, Vasilije (Cranfield University, 2019)
Dataset for publication: "Techno-economic feasibility assessment of calcium looping combustion using commercial technology appraisal tools", Journal of Cleaner Production
Keywords: 'efficiency penalty'; 'carbon capture'; 'clean power technologies'; 'clean coal'; 'economic assessment framework'; 'carbonate looping'; 'Power and Energy Systems Engineering (excl. Renewable Power)'